Effects of vegetation restoration on carbonate‐derived laterite erodibility in karst mountain areas. (1st April 2022) - Feng, Na; Liu, Dongdong; She, Dongli
Abstract: Vegetation restoration can exert a profound influence on surface soil characteristics, which likely plays a significant role in the evolution of soil erodibility. This study was conducted to quantify the effects of vegetation restoration on the soil erodibility of carbonate‐derived laterite in karst areas. Experiments were conducted at two representative sites for different years of vegetation restoration. Six karst mountain land use types [grassland (Y1), shrubland (Y2) and woodland (Y3) in young forest (YF); forest trails (O1), shrubland (O2) and woodland (O3) in old forest (OF)]. A structural equation model and random forest regression analysis were applied to distinguish the key environmental factors dominating soil erodibility. The results showed that the soil erodibility K factor exponentially decreased with increasing restoration age and tended to remain stable after 20 years ( y = 0.0466 + 0.0316 e −0.2889 x, R 2 = 0.98). The K factor in the OF decreased by an average of 2.1%–14.8% compared to those in the YF. A structural equation model indicated that vegetation restoration indirectly reduced soil erodibility by altering plant growth and coverage and its associated soil property changes. A random forest regression analysis of global datasets indicated that soil erodibility is mainly affected by topographical factors (i.e., latitude, elevation and slope), and their mean decrease accuracy values (IncMSE) exceeded 20%. Both forestland and shrubland were not considered as the most important factors for affecting global soil erodibility. Conversely, grassland, cropland and bare land were among the important factors. These results could guide the potential benefits of vegetation restoration strategies to meet soil conservation and ecosystem function goals in karst mountain ecosystems.